A Rapid and Efficient Screening System for Neutralizing Antibodies and Its Application for SARS-CoV-2 - Han, Xiaojian; Wang, Yingming; Li, Shenglong; Hu, Chao; Li, Tingting; Gu, Chenjian; Wang, Kai; Shen, Meiying; Wang, Jianwei; Hu, Jie; Wu, Ruixin; Mu, Song; et al. (Frontiers in Immunology, 2021)
After the pandemic of COVID-19, neutralizing antibodies (NAbs) against SARS-CoV-2 have been developed for the prophylactic and therapeutic purposes. However, few methodologies are described in detail on how to rapidly and efficiently generate effective NAbs to SARS-CoV-2. Here, we integrated and optimized a strategically screening method for NAbs, which has enabled us to obtain SARS-CoV-2 receptor-binding domain (RBD) specific NAbs within 6 days, followed by additional 9 days for antibody production and function analysis. Using this method, we obtained 198 specific Abs against SARS-CoV-2 RBD from the blood samples of COVID-19 convalescent patients, and 96 of them showed neutralizing activity. At least 20% of these NAbs exhibited advanced neutralizing potency and high affinity, with the top two NAbs showing half-maximal inhibitory concentration (IC50) to block authentic SARS-CoV-2 at 9.88 and 11.13 ng/ml, respectively. Altogether, our study provides an effective methodology with high applicable value for discovering potential preventative and therapeutic NAbs for the emerging infectious diseases.